Global private information in international equity markets☆ - Albuquerque, Rui; H. Bauer, Gregory; Schneider, Martin (Journal of Financial Economics, 2009)
This paper studies international equity markets when some investors have private information that is valuable for trading in many countries simultaneously. We use a dynamic model of equity trading to show that global private information helps explain US investors’ trading behavior and performance. In particular, the model predicts global return chasing (positive co-movement of US investors’ net purchases with returns in many countries) which we show to be present in the data. Return chasing in our model can be due to superior performance of US investors, not inferior knowledge or naive trend-following. We also show that trades due to private information are strongly correlated across countries. A common (global) factor accounts for about half their variation.